Entrepreneurial skill development in Indonesia and Nigeria through project-based learning - Muhammad Kristiawan; Henry Samuel Edosomwan; Sheren Dwi Oktaria; Elsa Viona (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2021)
This study aim to analyze how students in Indonesia and Nigeria used Project-Based Learning to develop their entrepreneurial skills. Qualitative methods with observation sheet and students’ project document were used as instruments in this study. The subjects were student whom join course entrepreneurship in Nnamdi Azikiwe University and Universitas Bengkulu. The success of the Project-Based Learning strategy is evaluated by reviewing projects completed by students. The results obtained in Nnamdi Azikiwe University and Universitas Bengkulu indicated that PjBL approach increases students’ entrepreneurship skill development, creative thinking, and problem solving. The findings of this study can be used by universities in Indonesia, Nigeria, and other countries as an alternative learning strategy. These are very important for everyone in the future. Hence, PjBL is an effective method that can be used to enhance the entrepreneurial skill of students compared to the traditional class structure where the teacher or lecturer do more of the teaching with less students’ involvement. This study provides an alternative option for developing entrepreneurial skills through project-based learning in both Indonesia and Nigeria.